Encephalitozoon hellem infection after haploidentical allogeneic hematopoietic stem cell transplantation in children: a case report - Shang, Yue; Ren, Yuanyuan; Liu, Lipeng; Chen, Xia; Liu, Fang; Li, Xiaolan; Wan, Yang; An, Wenbin; Yang, Wenyu; Zhu, Xiaofan; Guo, Ye (Frontiers in Immunology, 2024)
Background: Encephalitozoon hellem (E. hellem) infection is a zoonotic disease, rarely observed in individuals, causing various clinical manifestations including diarrhea, keratoconjunctivitis, cystitis, etc. E. hellem infection after hematopoietic stem-cell transplantation (HSCT) is a rare, serious complication. Case presentation: Herein, we present a case of E. hellem infection developing during HLA-haploidentical HSCT in a 9-year-old boy who suffered from aplastic anemia. On 15 days after HSCT, the patient developed recurrent and prolonged fever, diarrhea and hematuria. It is challenging to differentiate whether the symptoms mentioned in this case are caused by graft-versus-host disease (GVHD) or a specific infection. Based on the result of metagenomic next-generation sequencing (mNGS) and clinical observation, the patient was diagnosed as E. hellem infection, and received albendazole and decreased the immunosuppressive treatment. Finally, he had recovered. Conclusion: We should pay attention to the uncommon disease caused by the E. hellem infection after HSCT, especially in cases with immune reconstitution unrecovered. Among those rare infection, mNGS can be performed for better understanding the source of infection and targeted therapy, which can benefit the patients.